A STUDY OF EMOTIONAL INTELLIGENCE OF TENNIS PLAYERS AND SUBSEQUENT GENDER COMPARISON - Singh, Vikram; Banerjee, Debraj; Talreja, Arnav (International Journal of Research -GRANTHAALAYAH, 2024)
This research work was undertaken to study and compare the emotional intelligence of male and female tennis players from Delhi, NCR, India. The emotional Intelligence Scale (EIS- SANS) by Dr. Arun Kumar Singh and Dr. Shruti Narain was used as a tool in the present study. 70 state and national level tennis players (38 males and 32 females) in the age group of 16 to 21 years from various sports academies and schools in Delhi, NCR, India were randomly selected. Upon gender analysis, the study revealed that subjects showed the same level of emotional intelligence for both genders (p > .05). However, there seemed to be a difference between the male and female tennis players on understanding motivation (p < .05). partial correlation showed that there was no significant relationship between emotional intelligence and body mass index of tennis players while controlling for their age, r(67) = -.132, N = 70, p > .05.